Core competencies for family and community nurses: A European e-Delphi study. (March 2022) - Bagnasco, Annamaria; Catania, Gianluca; Zanini, Milko; Pozzi, Francesca; Aleo, Giuseppe; Watson, Roger; Hayter, Mark; Sasso, Loredana; ,; Rodrigues, Clara; Alvino, Serena; Musian, Daniele; et al.
Abstract: Aim: To identify the core competencies of family and community nurses. Background: The European Union is facing common health challenges in the field of primary care, according to European health policies and the World Health Organization, which need to be addressed through better and innovative ways of working that require joint actions. There is evidence that 'Family and Community Nurses' play a key role in the field of primary care, but there is no agreement on which core competencies they are required to have. Design: An e-Delphi study Methods: A 4-round e-Delphi study was conducted from March to July 2018 as part of the Erasmus+ Project "EuropeaN curriculum for fAmily aNd Community nursE" (ENhANCE). A panel of 23 experts from 10 European countries were asked to approve, modify, or add items and then prioritize each skill. Results: This e-Delphi, as part of the ENhANCE project, produced core 28 competencies, which were used by the "ENhANCE" partners to develop the European Core Curriculum for Family and Community Nurses. The ENhANCE partners ensured that the core competencies were consistent with World Health Organization recommendations, the European Skills/Competencies, Qualifications and Occupations (ESCO) and with the European Credit System for Vocational Education and Training (ECVET). Conclusions: The results of this study will provide the basis for universities across Europe to develop their own post-graduate teaching programs with common educational goals for Family and Community Nurses and a cadre of nurse practitioners with transferrable skills across the continent. Tweetable Abstract: This e-Delphi, as part of the ENhANCE project, produced 28 competencies for the European Core Curriculum for Family and Community Nurses. Highlights: First European study on core competencies for Family and Community Nurses. Family and Community Nurses core competencies used to develop European curricula. European common curricula will facilitate recognition and mobility of these nurses. Family and Community Nurses will improve the primary care of the European Union.